Arc flash assessment on photovoltaic grid connected system - Yahaya J.A.F.; Mansor M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Electric load flow; Electric network analysis; Energy conversion; Hazards; Protective clothing; Short circuit currents; Arc Flash; Comparative studies; Electrical power system; Grid connected systems; Personal protective equipment; Photovoltaic; Photovoltaic grid connected system; Renewable energies; Arc lamps